Peningkatan Sistem Akuntabilitas Kinerja Kemendagri melalui Cascading Perencanaan:: Alternatif Kebijakan dan Rekomendasi - VERLYANA RISYAH (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
This study aims to identify and outline policy alternatives to enhance the performance accountability system at the Ministry of Home Affairs (Kemendagri), with a focus on improving cascading planning. Although there has been an improvement in the Government Agency Performance Accountability System (SAKIP) of Kemendagri in 2024, evaluations indicate weaknesses in the process of cascading strategic goals to work units and individuals, as well as the use of indicators that still focus more on outputs than outcomes. Cascading planning, which ensures the alignment between the ministry's strategic goals and operational activities at all organizational levels, is considered the main approach to address these issues. This study uses a descriptive qualitative method, collecting data through document studies, in-depth interviews with relevant officials, and the analysis of performance evaluation documents from Kemendagri. The study proposes several policy options, including the improvement of cascading planning systems, optimization of the SIRIKA application, and strengthening performance evaluations down to the individual level. Additionally, the importance of using outcome-oriented indicators and applying SMART principles in planning and performance evaluation is emphasized. Policy recommendations include improvements in the development of the "Performance Tree," the creation of more relevant and measurable performance indicators, and the integration of more comprehensive information systems. With the proper implementation of these policies, it is expected that Kemendagri will achieve an A rating in the SAKIP evaluation, strengthen performance accountability, and drive bureaucratic reform that has a real impact on public services and regional governance.